SISTEM INFORMASI PEMESANAN TIKET BUS PADA CV.CHANDRA BAGAN BATU BERBASIS WEB - Arif Rahmad Hidayat; Volvo Sihombing; Deci Irmayani (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
Bus Chandra Bagan batu, is a service company engaged in the transportation sector. The method used by CV. Bus Chandra Bagan batu to order tickets, customers must come to the counter to order tickets. This makes it difficult for people to order tickets, especially if the weather is not supportive. So this bus ticket booking information system was created which aims to make it easier for customers to order bus tickets at CV.Bus Chandra. This information system is built using the PHP programming language and MySQL database and is supported by the local Xampp server. Through this information system, customers will find it easier to order bus tickets at CV. Bus Chandra Bagan batu.